Journeys towards decolonising research practices in Aotearoa New Zealand - S. Finlay-Smits; S. Manning; P. Edwards; M. Walton; C. Koroheke; M. Espig (Journal of Responsible Innovation)
This perspective piece focuses on attempts to reshape research in Aotearoa New Zealand in ways that honour Te Tiriti o Waitangi, the country's founding treaty between Māori and the Crown. These obligations establish dimensions of responsible research in this context that go beyond European-devised Responsible Innovation (RI) frameworks. We reflect on these requirements and how they are addressed within two public research organisations. Considering growing tensions between attempts to decolonise the Aotearoa science system and systemic challenges to enacting responsible research, we explore initiatives that seek to translate Te Tiriti obligations into research practices. While not articulated as RI, we discuss commonalities between these approaches and tenets of RI. Our reflections highlight the centrality of meaningful partnerships for enabling responsible research and the institutional structures required to support such relationships within Aotearoa. The paper concludes with questions around if, and how, the maturing RI scholarship can support decolonising research practices.